Kegunaan radiografi panoramik pada masa mixed dentition - Azda Nurma Himammi; Bambang Tri Hartomo (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2021)
Objectives: The purpose of this review is to determine the usefulness of panoramic radiography during mixed dentition and also to capture panoramic radiographs during mixed dentition. Review: Mixed dentition is a period of mixed dentition and a period of transition from sequential deciduous teeth followed by the eruption of the replacement tooth, namely the permanent tooth. The mixed dental phase occurs in children aged 6-12 years, beginning with the eruption of the first permanent tooth, usually a central incisor or mandibular first molar. Changes in occlusion occur significantly during this time due to the loss of the deciduous teeth and the eruption of the replacement permanent teeth. Conclusion: The mixed dentition period can be classified into 3 phases, namely. (1) the first transitional period, occurs at 6-8 years of age. In this phase, the eruption of the permanent first molars and the replacement of the deciduous incisors with the permanent incisors occurred. (2) the inter-transitional period, after the first molars and permanent incisors erupt, there is a transient period of about 1-2 years before the second transition phase begins. In this phase, it is called inter-transitional because the maxillary and mandibular arches consist of deciduous and permanent teeth. In the inter-transitional phase it is relatively stable and no changes occur. (3) the second transitional period at age (10-13 years), the date of the mandibular canine at about 10 years of age usually begins the second transitional period.